Cervical Cancer Presenting as an Omental Cake. (November 2018) - Canbaz, Fevziye; Celik, Handan; Kefeli, Mehmet; Tosun, Migraci
Abstract : Abstract: In women, peritoneal carcinomatosis usually originates from primary ovarian cancer. We report a case of omental cake as the initial presentation of a cervical cancer, which is extremely rare for this disease. 18 F-FDG PET/CT imaging demonstrated diffuse hypermetabolic abdominopelvic peritoneal carcinomatosis originating from cervical cancer that was confirmed by histopathologically.